Peptide inhibition of neutrophil-mediated injury after in vivo challenge with supernatant of Pseudomonas aeruginosa and immune-complexes. - Adrianne Enos; Parvathi Kumar; Brittany Lassiter; Alana Sampson; Pamela Hair; Neel Krishna; Kenji Cunnion (PLoS ONE)
Neutrophils are recognized for their role in host defense against pathogens as well as inflammatory conditions mediated through many mechanisms including neutrophil extracellular trap (NET) formation and generation of reactive oxygen species (ROS). NETs are increasingly appreciated as a major contributor in autoimmune and inflammatory diseases such as cystic fibrosis. Myeloperoxidase (MPO), a key neutrophil granule enzyme mediates generation of hypochlorous acid which, when extracellular, can cause host tissue damage. To better understand the role played by neutrophils in inflammatory diseases, we measured and modulated myeloperoxidase activity and NETs in vivo, utilizing a rat peritonitis model. RLS-0071 is a 15 amino acid peptide that has been shown to inhibit myeloperoxidase activity and NET formation in vitro. The rat model of inflammatory peritonitis was induced with intraperitoneal injection of either P. aeruginosa supernatant or immune-complexes. After euthanasia, a peritoneal wash was performed and measured for myeloperoxidase activity and free DNA as a surrogate for measurement of NETs. P. aeruginosa supernatant caused a 2-fold increase in MPO activity and free DNA when injected IP. Immune-complexes injected IP increased myeloperoxidase activity and free DNA 2- fold. RLS-0071 injection decreased myeloperoxidase activity and NETs in the peritoneal fluid generally to baseline levels in the presence of P. aeruginosa supernatant or immune-complexes. Taken together, RLS-0071 demonstrated the ability to inhibit myeloperoxidase activity and NET formation in vivo when initiated by different inflammatory stimuli including shed or secreted bacterial constituents as well as immune-complexes.